1985
DOI: 10.1152/ajpheart.1985.248.6.h859
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar inflammation and arachidonate metabolism in monocrotaline-induced pulmonary hypertension

Abstract: We tested the hypothesis that monocrotaline would activate arachidonic acid metabolism in rats. If activation occurred before the pulmonary hypertension developed, arachidonate metabolites could play a role in the hypertensive monocrotaline injury. We found that 1 wk after monocrotaline administration 6-ketoprostaglandin F1 alpha and leukotriene C4 were increased in lung lavages. At 3 wk when pulmonary hypertension was well developed, lung lavage contained increased 6-ketoprostaglandin F1 alpha and thromboxane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 0 publications
0
39
0
Order By: Relevance
“…MCTinduced pulmonary endothelial injury is known to be followed by significant pulmonary vascular and alveolar inflammation (34,40), and the latter is thought to be important in subsequent pulmonary vascular remodeling and pulmonary hypertension. Previous studies have shown that inhibition of inflammation by interleukin-1 receptor antagonists (37) or by an antibody that neutralizes monocyte chemotactic and activating factor/monocyte chemoattractant protein-1 (19) alleviate MCT-induced pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MCTinduced pulmonary endothelial injury is known to be followed by significant pulmonary vascular and alveolar inflammation (34,40), and the latter is thought to be important in subsequent pulmonary vascular remodeling and pulmonary hypertension. Previous studies have shown that inhibition of inflammation by interleukin-1 receptor antagonists (37) or by an antibody that neutralizes monocyte chemotactic and activating factor/monocyte chemoattractant protein-1 (19) alleviate MCT-induced pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted disruption of the 5-LO gene (38) or treatment of animals with diethylcarbamazine (24), MK-886 (an inhibitor of FLAP) (38), or leukotriene antagonists (1,16,23,31) reduced hypoxia-induced pulmonary hypertension. Diethylcarbamazine, an antiparasitic drug that also inhibits 5-LO, was shown to ameliorate the development of pulmonary hypertension caused by monocrotaline (MCT) in rats (34).…”
mentioning
confidence: 99%
“…MCT is known to cause pulmonary endothelial injury and pulmonary hyper-tension in humans and rats (39) but has little effect in mice (30). 5-LO and its products, leukotrienes, have been previously found to mediate or facilitate the MCT-induced pulmonary hypertension in rats (37,42). We have previously shown that addition of Ad5LO to MCT challenge in rats significantly exacerbates the pulmonary hypertension caused by MCT (17).…”
mentioning
confidence: 91%
“…Early pathological changes include pulmonary artery endothelial swelling and blebbing (11) and alveolar inflammatory infiltrates (15,16). The subendothelial space appears widened (17)(18)(19), associated with a slight increase in the number of small breaks in the inner elastic lamina compared with normal pulmonary arteries (17).…”
Section: Introductionmentioning
confidence: 99%